Determinants of job satisfaction among employees at Parkson Mahkota Parade, Melaka / Halimatul Sadiah Abd. Ghafar - Abd. Ghafar, Halimatul Sadiah (Faculty of Business and Management, 2013)
This chapter serve as general as general of the research. It will provide the background of the study, purpose and scope of the study, significant of the study as well as the limitation of the research.